Evidence of microplastic-mediated transfer of PCB-153 to sea urchin tissues using radiotracers. (December 2022) - Pyl, Marine; Taylor, Angus; Oberhänsli, François; Swarzenski, Peter; Besson, Marc; Danis, Bruno; Metian, Marc
Abstract: The present study reports the first experimental microplastic-mediated transfer of a key PCB congener into adult specimens of the sea urchin Paracentrotus lividus . Three experiments were conducted to assess whether 14 C-PCB-153 adsorbed onto negatively buoyant microplastics (MPs) (500–600 μm) is bioavailable to the sea urchin: (1) exposure to a low concentration of 14 C-PCB-153 sorbed onto a high number of virgin MPs ("lowPCB highMP" experiment), (2) exposure to a high concentration of 14 C-PCB-153 sorbed onto a relatively low number of virgin MPs ("highPCB lowMP" experiment), and (3) exposure to a low concentration of 14 C-PCB-153 sorbed onto a relatively low number of aged MP ("lowPCB lowMP" experiment). Results showed that the transfer of 14 C-PCB-153 from MPs to sea urchin tissues occurred in each of the three 15-day experiments, suggesting that MPs located on the seafloor may act as vectors of PCB-153 to sea urchins even during short-term exposure events. Graphical abstract: Unlabelled Image Highlights: Microplastic particles (MPs) acted as vectors of 14 C-PCB-153 to sea urchin tissues in all experimental tested conditions. The degree of transfer of 14 C-PCB-153 from the MPs to body compartments is related to the level of 14 C-PCB-153 exposure. The MP-mediated transfer of PCB was higher in sea urchins exposed to virgin MPs rather than those exposed to aged MPs. The dominant route of transfer of PCB from MPs occurred via plastic ingestion, followed by dermal sorption.